(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2025)
This paper presents an analysis of the surface roughness during turning of hardened 42CrMoS4 steel using a quick-change tool holder with innovative design. The experiments used a Swiss-type CNC lathe - GOODWAY SW-20. The process was performed at cutting speed of 130 to 170 m/min, feed of 0.12 to 0.18 mm/tur and cutting depth of 1.5mm. Based on the results obtained, a mathematical model was developed, the graphic interpretation of which is presented in two-dimensional and three-dimensional coordinate systems. The mathematical model was used in the dispersion analysis to determine the influence of speed and feed during turning on the roughness of the machined surface. Graphical relationships are presented for the influence of the controlling factors on roughness.